3(b-5)=27

Simple and best practice solution for 3(b-5)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(b-5)=27 equation:



3(b-5)=27
We move all terms to the left:
3(b-5)-(27)=0
We multiply parentheses
3b-15-27=0
We add all the numbers together, and all the variables
3b-42=0
We move all terms containing b to the left, all other terms to the right
3b=42
b=42/3
b=14

See similar equations:

| -11k+126=62-3k | | 9/y=72/80 | | -5=3m=-14 | | -2(4+4v)-v=-44 | | 10p+63=33 | | 49+x=434 | | m=14-10=-11 | | 3(2x-5x)=3x+4x | | 40=0.5(96-x) | | 1m-4=1 | | x÷3=69 | | 5m2-54=0 | | 8x–23=3x+27 | | -7x-15=-15x+9 | | m−4=1 | | y=3/4(-4)+1 | | w+11/10=10 | | y=3^2+23+5 | | 4(3x-6)=30 | | -6=-6(8+n) | | 2(3x+4.5)=90 | | 2(3x=4.5=)90 | | -7+n=7=-5 | | 7=12-t/9 | | 4h−–3=11 | | 5x-3÷2=11 | | 3/4y=-18 | | -12=5(6x+4)+7(x+7) | | -2(x+2)+3x=x | | 14=h/6+8 | | 399+x=413 | | 4x-2=x-18 |

Equations solver categories